INTRODUCTION AND CONSENSUS BEST PRACTICES FOR SKILLED NURSING FACILITY TO HOME TRANSITIONS - Carnahan, J. (Innov Aging, 2017)
Community-dwelling patients treated in U.S. skilled nursing facilities (SNFs) after an acute hospitalization have a high incidence and prevalence of comorbidities and geriatric syndromes. These patients are also high risk for poor outcomes such as death and hospital readmission. This presentation will provide an introduction to the SNF model of care and to characteristics of this patient population, their epidemiology, and their healthcare outcomes and needs. Finally, the Best Practices will be briefly outlined to lay the groundwork for the following presentations, which will highlight practical steps to implementation.